Positive relationship of trunk movements and acceleration during 20m sprint test in elite male football players - Sos, K.; Mikulic, P. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to investigate the association between trunk movements and whole-body acceleration, velocity and performance time during an all-out 20 m sprint test. This study encompassed 21 male top level football players. The participants were equipped with a Catapult OptimEyeX4 device that included a GPS sensor, an accelerometer and a gyroscope. The results indicated that average angular velocity about the vertical axis correlated with maximal whole body acceleration. Furthermore, the sum of angular velocities about all three axes correlated with maximal acceleration. However, maximal acceleration did not correlate with maximal velocity and sprint performance time, while average acceleration did. The findings point to the importance of trunk movements, especially rotation about the vertical axis, for developing a player's maximal acceleration.